Preliminary effectiveness of social prescription and virtual patient information in increasing tertiary prevention among cancer patients (ESPRIT): protocol for a single-centre, randomised controlled pilot trial - Karen Steindorf; Michael Koller; Michael Leitzmann; Wolfgang Herr; Daniel Heudobler; Lisa Boyer; Anne Herrmann; Tobias Pukrop; Christine Bernardi; Sabine Einhell (BMJ Open)
Introduction Tertiary prevention through physical activity and psychosocial support can positively impact patient outcomes, such as physical function and quality of life (QoL). However, more research is required on the effectiveness of strategies designed to increase the uptake of tertiary prevention programmes among cancer patients. Here, we present the protocol for a single-centre, randomised controlled pilot trial testing the preliminary effectiveness of social prescription and virtual patient information in increasing tertiary prevention among cancer patients and support persons (SPs) (ESPRIT “Effectiveness of a social prescription and virtual patient information in increasing tertiary prevention” pilot trial).Methods and analysis Cancer patients attending medical oncology units at a university hospital in southern Germany and their SPs will be randomly allocated as a dyad to group A (social prescription (n=36)), group B (virtual patient information (n=36)) or group C (usual care (n=36)). The hospital is part of a Comprehensive Cancer Centre mainly treating patients living in rural areas. Primary outcomes are the uptake of physical activity, participation in social activities and psychosocial support. Secondary outcomes are overall QoL, knowledge of the health benefits of physical activity and psychosocial support and self-efficacy of patients. The outcomes will be assessed at baseline and after 3, 6 and 12 months of follow-up. Physical activity will be assessed using accelerometers and measured by average steps per day within the last 2 weeks after recruitment and at follow-up visits (3, 6 and 12 months). Cost-effectiveness and the time spent in the consultation, as well as potential implementation barriers and facilitators, will also be explored as part of a mixed-methods hybrid design. All data will be summarised descriptively. Regarding the analysis of primary endpoints, the average number of steps per day, as well as the summary score of the social activity log and self-report on the use of psychosocial support, will be compared between the groups (A, B and C) using analysis of variance, followed by Dunnett’s test for pairwise comparisons of the intervention groups against the control group. Mean differences and 95% CIs will be presented as effect estimates. The analysis of secondary endpoints will include appropriate statistical methods such as the χ2 test of independence or linear regression models, which will be used to analyse secondary endpoints and to investigate factors influencing preliminary effectiveness.Ethics and dissemination This trial has been approved by the ethics committee of the University of Regensburg (reference: 23-3317-101). Signed written informed consent is required from all study participants. The results of the study will be used to inform the power calculation for future confirmatory trials and will be submitted for publication.Trial registration number DRKS00033771.